THE ROLE OF PRINCIPLES OF A FINAL CLINICAL DIAGNOSISIN FORMATION THE STRUCTURE OF MATERNAL MORTALITY - E. Yu. Lebedenko; A. P. Milovanov; A. F. Michelson; I. M. Rozenberg (Медицинский вестник Юга России, 2014)
Purpose: To evaluate the role of statement, classification and comparison of final clinical and pathologic diagnosis in the structure formation of maternal losses,Materials and Methods: A posthoc analysis of medical records of 74 deaths of pregnant, parturient and puerperal women, registered in the obstetrics institution in the Rostov region from 2000 to 2007.Results: Non-classified final clinical diagnosis (chronological registration of symptoms, lack of headings of underlying disease, fatal complications, accurate dating of surgical measures and major components of remedial and resuscitation measures) objectively reflects the diagnosis defects of prime causes of maternal deaths and wrong treatment policy.Summary: Detailed clinical analysis of the causes of maternal deaths, comparison of the final and pathologic diagnosis clarifies the actual nosological profile of maternal mortality and its intensive parameters, as well as determines the reserves of its further decrease.